Nigerian Literature and Current Realities: The Challenge of Illiteracy and E-Literacy (Global Journal of Human-Social Science, 2016)
Today's world is becoming more and more technology-driven, and the speed of change in technology has become neck-breaking, mind-breaking and intractable to many related fields. Literature is one of such fields that have much to do with the information technology, particularly in relation to language use and retrieval and utilization of information resources -activities that require high or relatively high level of literacy. This paper examines the issues of illiteracy and e-literacy as some of the challenges confronting the 21 st century Nigerian literary writer, critic and reader. Hence, it has three trajectories: the Nigerian writer's use of information technology as a tool for propagating African literature; the Nigerian critic's use of information technology as a tool for propagating the criticism of African literature; and the Nigerian reader's use of information technology as a tool for accessing African literature. The study looks at the response of the Nigerian literary scholar to the global requirement of e-literacy against the backdrops of poor reading culture and high rate of illiteracy in Nigeria.
Keywords: illiteracy; e-literacy; information; communi-cation; technology; literature; globalization